Childlessness in Lithuania: Trends, Norms and Spatial Differentiation - Gedvilaitė-Kordušienė, Margarita; Tretjakova, Vaida; Ubarevičienė, Rūta (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English]During the last decades, the share of childless women has been on the rise in the majority of European countries. Consequently, the phenomenon of childlessness has been receiving more attention in the scientific discourse. Usually, it is investigated as one of the manifestations of family transformation occurring in modern societies that is related to changing family models and gender roles.Even though, when compared to other European countries, the share of childless women in Lithuania remains low, it has recently increased both in terms of permanent (among women above reproductive age) and temporary (among women of reproductive age) childlessness. However, so far this subject has been underresearched. In this paper, we aim to examine the trends in women’s permanent childlessness, reveal the sociodemographic characteristics of childless women born in 1920–1969 and explore the spatial differentiation of childlessness in Lithuania. The empirical basis of our analysis consists of a couple of secondary data sources: the third wave of the European Values Study (2008), the Lithuanian Population Census (2011).An analysis of cultural norms regarding childlessness has revealed an ambivalence in attitudes. On the one hand, respondents have expressed support for individualistic attitudes, stating that an individual has the right to decide whether to have a child or not. On the other hand, there was substantial support for the familialistic norm that children give meaning to life, especially for women.In terms of the sociodemographic characteristics, the biggest differences between childless women and mothers occur in relation to marital status and education. Throughout all generations, a significantly higher proportion of childless women in comparison to mothers remain unmarried. Since marriage was the primary pathway to family formation in earlier times, it is plausible that the majority of women in older cohorts have become childless due to certain circumstances – failure to find a (suitable) partner. On the other hand, younger generations have been influenced by the family transformation, which in Lithuania started around 1990 and brought changes in family formation and procreative behavior. Therefore, it is likely that voluntary childlessness is more common among childless women in younger generations.A spatial analysis of childlessness has revealed that this demographic process in Lithuania has a high degree of regional differentiation, especially from the 1940–1949 cohort and onwards. With the exception of the oldest cohort, throughout all generations, the highest share of childless women – higher than 10 percent – is observed in Vilnius and other major city municipalities. Additionally, we observe higher degrees of childlessness in certain areas of north and northeast Lithuania. The majority of the municipalities in this region have the status of “sparsely populated territories” and are considered “problematic” in terms of other demographic, social and economic indicators in the scientific discourse of human geography in Lithuania. The results of the analysis of the spatial differentiation of childlessness might be useful for forecasting the development trends of childlessness in the future across the different regions of the country. However, more in-depth research is needed in order to identify the specific factors affecting the regional differentiation of childlessness in Lithuania.
Keywords: Childlessness; European social research; Lithuanian populiation census; Lithuania